130 Reproducibility of T1 and T2 Mapping in Health and Disease, and Assessment of T2 Variability Across the Normal Myocardium. (31st May 2014) - Puntmann, Valentina; Foote, Lucy; Hinojar Baydes, Rocio; Higgins, David; Nagel, Eike
Abstract : Background: T1 and T2 mapping detect myocardial fibrosis and oedema respectively. T1 values show segmental variation in mid ventricular SAX slice, making the identification of regional pathology difficult.We tested the reproducibility of T1 and T2 mapping in health and disease and regional variations of T2 values. Methods: Patients with non-ischaemic cardiomyopathy (NICM, n-10), ischaemic heart disease (IHD, n-10) and 10 controls underwent T1 and T2 mapping in a single SAX slice on a 3T scanner using MOLLI and T2 multi-echo sequence. Two independent observers measured T1 and T2 values from quantitative maps in six standardised regions of interest. Intra- and inter-observer reproducibility of T1 and T2 mapping was assessed using Bland-Altman plots and Pearson's correlation. Results: Age was significantly higher in IHD group (p < 0.05). Patients with NICM had increased EDV (p < 0.05), IHD patients had increased ESV (p < 0.05) and decreased EF (p < 0.05). Intra- and inter-observer agreements for T1 (r = 0.988; r = 0.965) and T2 (r = 0.978; r = 0.948) values across the whole cohort were very high (p < 0.001 for all agreements). Similarly, the intra- and inter-observer coefficients of variation (CoV) for T1 (0.66%; 1.19%) and T2 (1.85%; 2.5%) values were low. There was no significant difference between segmental T2 values in theSAX slice (p = 0.205). Conclusions T1 and T2 mapping are highly reproducible techniques. T2 maps show no segmentalvariation. Our study suggests that a single normal range of T2 values could be applied to the entire mid-ventricular SAX slice. Future work should aim to create a normal range of T2 values for this purpose.